PEER TUTORING IN ACADEMIC WRITING - Prisila, Monika; Rufinus, Albert (English Language Education Study Program, 2024)
Peer tutoring in academic writing is a kind of peer-assisted teaching-learning strategy that provides the opportunity for students to facilitate other students in a collaborative way of learning writing. In pairs or groups, the student may learn not only academic, but social, behavioral, and functional skills as well. Many different ways to pair students, such as by ability level, skills mastered, or age. Indeed, to help each student with their particular writing issues, peer tutoring is necessary as an opportunity to offer extra lessons. Up-to-date, the Coronavirus pandemic's extensive effects have led to more and more educational institutions offering training and instruction online. Most schools and higher institutions in West Kalimantan use digital technology in their instructional program. However, because online sessions are usually held in big groups and have internet limitations, it might be difficult for the lecturer to keep track of all of their students. Incorporating peer tutoring via digital means can be an alternative to meet the students needs in online learning